Prima del film. "Ephemeralia" del regista e storia materiale della produzione (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
The article aims to excavate the room of the film director, in the realm of ephemeral and everyday life, by focusing on scrapbooks. It begins with the belief that, to focus attention on these kinds of materials can offer a better understanding of certain, crucial nodes of film production and development practices; and furthermore that it can unveil elements of the theory and methodology of writing the history of film production and development. For instance, the use of ephemeral media as meta-history, where the “maker” leaves traces of his/her productive activity. This article focuses on a constellation of material traces that emerge when excavating the private archive of Dino Risi, held by his son, Marco Risi. It is a relevant occasion to open a cultural and anthropological perspective on the very early stages of the film storytelling.